Bem jurídico penal e Constituição - Oliveira, Miguel Tassinari de (2010)
To present research it seeks to delineate the limits imposed to the make law activity in what plays the elaboration of criminal laws. It is reached the end longed for by the formatting of a material concept of crime, that has well for essence the notion juridical penal, while well, value or indispensable interest to the maintenance of the life in society. The crime comes, under mentioned it material aspect, as the violation or the exhibition to danger of a juridical good protected by the criminal law. It comes the Constitution of the State as only instrument to be able for revealing the juridical goods worthy of penal protection, because it is in itself, explicit or implicitly, the goods, values or indispensable interests are estabilished to the preservation of the social body and the appropriate development of the personality of their members. Also because if the feather implicates the restriction constitutionally of well estabilished (freedom or property) it is reasonable, even for a proportionality subject, that is only used as instrument of protection of a good that even shows constitutional relevance. But the simple penal dignity of the juridical good, revealed by its constitutional estabilishment, it doesn't come as enough to authorize the lawmaker to promote his protection through the criminal law, being demanded, still, the verification of the lack of the intervention of the State through the prohibition or imposition of a conduct by the threat of punishment, which, in rule, it is made case to case by the lawmaker. In rule because there are hypotheses of constitutional impositions of criminalization of conducts to confront certain juridical goods, in which the constitucional lawmaker calls for himself the incumbency not only of proclaiming the penal dignity of the as well as of attesting the lack of her protection by the criminal law. Such hypotheses of criminalization constitutional impositions are analyzed, as well as the consequences and the gears for cohibiting the disrespect of the lawmaker to them